Lingua sensibile al genere nella comunicazione istituzionale della Confederazione svizzera: analisi di un corpus parallelo tedesco-italiano - Nicoli, Roberto (Linguistik Online, 2025)
This paper aims to analyse the use of gender-sensitive language in the Swiss Confederation’s institutional communication, with particular reference to German and Italian. The first part examines the similarities, differences and peculiarities in the visibility and neutralization strategies set out in the guidelines on gender-inclusive language for the two idioms considered. The second part describes the extent to which and the ways in which these guidelines are applied and outlines the prevailing trends in current Swiss legal and administrative communication practice. This is carried out by examining a parallel corpus of official texts (such as ordinances, regulations, decisions, exchanges of notes, conventions, federal laws, amendments, protocols, agreements, reports, explanatory notes and press releases) from the first half of 2025, through the use of the Sketch Engine language analysis software.